Another diophantine equation

{ x 2 + y z = 42 x + y 2 z = 18 \large \begin{cases} x^{2}+y-z=42 \\ x+y^{2}-z=18 \end{cases}

How many integer solutions are there to the system of equations above?


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Subtracting the second of the given equations from the first yields the equation

x 2 x ( y 2 y ) = 24 ( x 1 2 ) 2 ( y 1 2 ) 2 = 24 x^{2} - x - (y^{2} - y) = 24 \Longrightarrow (x - \frac{1}{2})^{2} - (y - \frac{1}{2})^{2} = 24 \Longrightarrow

( 2 x 1 ) 2 ( 2 y 1 ) 2 = 96 ( 2 x 1 ( 2 y 1 ) ) ( 2 x 1 + ( 2 y 1 ) ) = 96 (2x - 1)^{2} - (2y - 1)^{2} = 96 \Longrightarrow (2x - 1 - (2y - 1))(2x - 1 + (2y - 1)) = 96 \Longrightarrow

( 2 ( x y ) ) ( 2 ( x + y 1 ) ) = 96 ( x y ) ( x + y 1 ) = 24 (2(x - y))(2(x + y - 1)) = 96 \Longrightarrow (x - y)(x + y - 1) = 24 .

Now 24 = 2 3 × 3 24 = 2^{3} \times 3 has ( 3 + 1 ) ( 1 + 1 ) = 8 (3 + 1)(1 + 1) = 8 positive divisors, and thus 16 16 integer divisors. We can then assign ( x y ) (x - y) and ( x + y 1 ) (x + y - 1) values in 16 16 different ways. For example, we could have

x y = 24 , x + y 1 = 1 ( x y ) + ( x + y 1 ) = 24 + ( 1 ) x - y = -24, x + y - 1 = -1 \Longrightarrow (x - y) + (x + y - 1) = -24 + (-1) \Longrightarrow

2 x 1 = 25 x = 12 , y = 12 , z = x 2 + y 42 = 114 2x - 1 = -25 \Longrightarrow x = -12, y = 12, z = x^{2} + y - 42 = 114 .

Similarly x y = 1 , x + y 1 = 24 x = 12 , y = 11 , z = 91 x - y = -1, x + y - 1 = -24 \Longrightarrow x = -12, y = -11, z = 91 .

However, for x y = 12 , x + y 1 = 2 2 x 1 = 14 x - y = -12, x + y - 1 = -2 \Longrightarrow 2x - 1 = -14 , we do not obtain an integer value for x x . Only in those cases where the factor pairs add to an odd number will we get integer values for x , y x,y . There are 8 such factor pairings, including the pair 24 × 1 -24 \times -1 mentioned above. The other 7 are

1 × 24 , 3 × 8 , 8 × 3 , 3 × 8 , 8 × 3 , 1 × 24 -1 \times -24, -3 \times -8, -8 \times -3, 3 \times 8, 8 \times 3, 1 \times 24 and 24 × 1 24 \times 1 .

Each of the 8 factor pairings yields a distinct integer triple ( x , y , z ) (x,y,z) , so the given system of equations has a total of 8 \boxed{8} solutions.

Same here mate, only a slightly different beginning, perhaps simpler:

From x 2 x ( y 2 y ) = 24 x^2 - x - (y^2 - y) = 24 you could say that x 2 y 2 ( x y ) = 24 x^2 - y^2 - (x - y) = 24 , and then ( x + y ) ( x y ) ( x y ) = 24 (x+y)(x-y) - (x-y) = 24 , or ( x + y 1 ) ( x y ) = 24 (x+y-1)(x-y) = 24 , without needing to use squares :)

Guilherme Niedu - 4 years, 3 months ago

Log in to reply

Yes, much more elegant. :)

Brian Charlesworth - 4 years, 3 months ago

We see after substracting both the equations that 24= difference of products of two consecutive integers . Consider first only positive ones. It is not hard to see that 24= 13x12-12x11. Therefore the pair having minimum difference is above one. Now writing down all products till 13x12.

It is again not hard to see the only other pair is , that is , 24= 6x5-3x2.

For each pair we have 4(including negative ones).

Answer=8

Aakash Khandelwal - 4 years, 3 months ago

I do believe there is a viable solution for counting roots via Vieta Root Jumping to cut down on the number of solutions we need to determine.

Sharky Kesa - 4 years, 3 months ago

Can we solve it using Pell"s equation??

ppk k - 4 years, 3 months ago

Log in to reply

The general Pell equation is of the form x 2 n y 2 = 1 x^{2} - ny^{2} = 1 for any n N n \in \mathbb{N} , so I'm not sure that it would really apply here.

P.S.. That wasn't me who down-voted your comment. I don't know why anyone would downvote a legitimate inquiry such as yours.

Brian Charlesworth - 4 years, 3 months ago
Leonel Castillo
Jul 18, 2018

Solve for z z in two different ways to simplify the equation into x 2 x ( y 2 y ) = 24 x^2 - x - (y^2 - y) = 24 . Divide by two on both sides: x 2 x 2 y 2 y 2 = 12 \frac{x^2 - x}{2} - \frac{y^2 - y}{2} = 12 . What we have is that the difference of two triangular numbers is equal to 12. But we know that the difference of two triangular numbers is always the sum of consecutive positive integers so we must ask, in how many ways can we write 12 as a sum of consecutive integers?. It is just an easy computation, 12 = 3 + 4 + 5. No other solutions exist. To which triangular numbers do these correspond? Well, 12 = 12 12 = 12 just corresponds to the difference k = 1 12 k k = 1 11 k \sum_{k=1}^{12} k - \sum_{k=1}^{11} k . So T x = 78 , T y = 66 T_x = 78, T_y = 66 . It is important to note that when solving for the values of x , y x,y we will be solving quadratic equations with two distinct solutions, so we know this will generate 2 × 2 = 4 2 \times 2 = 4 possible solutions.

To conclude, 12 = 3 + 4 + 5 12 = 3 + 4 + 5 corresponds to the difference k = 1 5 k k = 1 2 k \sum_{k=1}^{5} k - \sum_{k=1}^2 k . That is, T x = 15 , T y = 3 T_x = 15, T_y = 3 . As before, this will generate 4 more solutions for a grand total of 8.

Abhiram Bondada
Apr 2, 2017

When we subtract equation 2 from 1 we get this after simplifying the result (x-y)(x+y-1)=24

If we factorize 24 into product of 2 numbers we get 8 different possible pairs of numbers they are:-

(1,24) (24,1) (2,12) (12,2) (3,8) (8,3) (4,6) (6,4) in these pairs we can allot these values to any one of the two terms in x,y [x-y and x+y-1] and get 8 values for x and y. As x,y are integers from the solutions we can say z is also integer by closure property and thats it its done.

Ans: 8

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...